Colour coding subtitles in multilingual films – a reception study. - Szarkowska, Agnieszka; Boczkowska, Julianna (Perspectives: Studies in Translatology, 2022)
Multilingual films do not always travel well across borders. When translated, multilingualism may become neutralised and washed out. In subtitling, multiple languages used in the original are usually not marked in any way in the target subtitles. This results in neutralisation and linguistic homogenisation, whereby target viewers may not even realise that different languages are spoken in the film. In this study, we test a new solution aimed to help preserve the multilingual nature of films in interlingual subtitling: the strategy of colour coding. To gauge the impact of colour coding on viewers, we conducted a survey-based reception study on a group of 52 Polish hearing speakers who watched a multilingual film with interlingual subtitles in two versions: one where subtitles were coloured, i.e. each language was marked with a different colour, and the other, control condition, where the subtitles were traditionally white. We measured participants' immersive tendency, immersion, comprehension, and cognitive load. While colour coding did not have a significant impact on immersion, we found that individuals with a lower tendency for immersion reported higher immersion levels when watching coloured subtitles. Our results may contribute to the discussion how to render the multilingual nature of films in interlingual subtitling.